Strategi Pendidikan Yang Memerdekakan Dalam Mengembangkan Keterampilan Abad 21 - Angel Claudia Situmeang; Liesna Andriany (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The focus on 21st-century skills has become a primary concern in education today, especially in the PPL school environment at SMA Negeri 3 Medan. This research aims to identify and analyze liberating educational strategies in developing 21st century skills in the school. The research method used is a qualitative approach with a case study method. Data was collected through interviews with teachers, classroom observations, and analysis of educational documents. The research results show that SMA Negeri 3 Medan has implemented several liberating educational strategies, such as project-based learning, collaboration between students, and empowering students in the learning process. These strategies are designed to improve 21st century skills, such as problem solving, critical thinking, collaboration, communication, digital literacy, and emotional skills. However, there are still several challenges faced by SMA Negeri 3 Medan in implementing liberating education strategies. Therefore, a strong commitment is needed from all relevant parties to continue to develop and strengthen liberating educational strategies to prepare students to face the demands of the 21st century.